PENGUATAN MANAJEMEN INVESTASI KELOMPOK MASYARAKAT PEMBUDIDAYA IKAN NILA KELURAHAN DEGAYU KOTA PEKALONGAN - Linayati - Linayati; Tri Yusufi Mardiana; Wijianto Wijianto; Ashari Fahrurrozi; Muhammad Zulkham Yahya (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2023)
Indonesia as a country that has abundant natural resources, especially waters, causes the fishery sector to become one of the sectors with great potential in development. One of the efforts to improve the human resources of coastal communities is to form institutions at the farmer level, but there is a lack of insight and knowledge about the function of farmer institutions as a forum for the organization. The purpose of this community service is to increase and increase knowledge for the community about the importance of institutions in managing businesses in the fisheries sector, especially in investing. The method used by explaining directly or presenting to community groups who attended the counseling with participants was the MAPAN group from Degayu Village, Pekalongan City with 25 members. The result was that 80% of participants were able to capture knowledge about the importance of institutions for developing fishery businesses after being given counseling and the community was able to compile data on investment in institutions that were formed after receiving counseling.Â Keywords: Organization, Investment, Society